Still seeking, still fighting. Issue 3 (3rd July 2016) - Mackby, Jenifer
ABSTRACT: Arms-control advocates have traveled a long road to end nuclear testing. Beginning with the US Baruch Plan and the Soviet Gromyko Plan in 1946, negotiations led to the signing of the Comprehensive Nuclear-Test-Ban Treaty (CTBT) in 1996. Two decades later, a verification regime is up and running, with most of a planned 337 facilities installed around the globe and sending information to a data center in Vienna. Large-scale on-site inspection exercises in Kazakhstan, Jordan, and elsewhere have shown that the planned procedures work. What is missing? Of the forty-four countries that must ratify the treaty for it to enter into force, eight still must proceed with their national measures for ratification. How and why did the negotiators end up with such an unwieldy provision? How did they design such a complex international monitoring system so quickly? This article delves into a brief history of the treaty and its negotiations, highlighting some of the key and most contentious articles of the CTBT, painstakingly arrived at. These include the basic obligations, entry into force, and certain verification issues, including on-site inspections. It also examines the interface of science and technology with diplomacy and politics. Senior diplomats and world-renowned scientists convened in Geneva day and night to hammer out the complex issues involved in verifying compliance with a test ban. They devised a regime that has exceeded their expectations.